Plasma IgG antibody against cytomegalovirus but not herpes simplex virus is associated with recurrence of atrial fibrillation after catheter ablation. (1st March 2016) - Liu, Shaowei; Liu, Nian; Ruan, Yanfei; Li, Xin; Wen, Dan; Chen, Lizhu; Guo, Xueyuan; Guo, Lizhu; Jiang, Chenxi; Long, Deyong; Yu, Ronghui; Tang, Ribo; et al.
Abstract: The precise mechanism of atrial fibrillation (AF) remains uncertain but suggested to be correlated with pathogenic infection. This study sought to determine the role of viral pathogens, herpes simplex virus (HSV)-1, HSV-2, and cytomegalovirus (CMV), in AF recurrence after radiofrequency catheter ablation in a strictly selected patient population. A total of 4148 patients undergoing AF catheter ablation were screened for structural heart diseases and known risk factors for AF, and the resultant 103 patients (74 paroxysmal and 29 persistent) were recruited. Pre-ablation clinical and laboratory data and viral-specific IgG antibody levels were compared with those in 72 healthy control subjects. Plasma concentrations of the antibodies were all significantly elevated in AF patients ( P < 0.001 vs. control). During a mean follow-up of 12.8 ± 7.0 months, 29 (28.2%) patients had AF recurrence. Patients who experienced AF recurrence had a significantly higher concentration of baseline anti-CMV, but not anti-HSV, IgG antibody than non-recurrent patients in the overall AF population ( P = 0.01) and in subgroup analysis of persistent AF patients ( P < 0.001). Multivariate Cox regression analysis indicated that anti-CMV level independently predicted post-ablation AF recurrence in both the overall AF patients [hazard ratio (HR) 1.013, P = 0.029] and persistent AF patients (HR 1.034, P = 0.043). Circulating anti-CMV IgG level may have important prognostic value in determining AF recurrence in post-ablation patients beyond established risk factors.